2013
DOI: 10.1093/hmg/ddt104
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association and longitudinal analyses reveal genetic loci linking pubertal height growth, pubertal timing and childhood adiposity

Abstract: The pubertal height growth spurt is a distinctive feature of childhood growth reflecting both the central onset of puberty and local growth factors. Although little is known about the underlying genetics, growth variability during puberty correlates with adult risks for hormone-dependent cancer and adverse cardiometabolic health. The only gene so far associated with pubertal height growth, LIN28B, pleiotropically influences childhood growth, puberty and cancer progression, pointing to shared underlying mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
195
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(207 citation statements)
references
References 43 publications
7
195
0
Order By: Relevance
“…Another increasingly popular approach is Mendelian randomization, which addresses unmeasured and residual confounding by using genetic polymorphisms as instrumental variables for the exposure of interest, based on their random allocation at conception resulting in their independence of confounding factors 43. However, the potential to use Mendelian randomization to study age at menarche in relation to cardiometabolic health is hampered by the number of overlapping genes associated with both age at menarche and adiposity 20, 31. Longitudinal studies with measures of adiposity before and after puberty have the potential to contribute valuable insight into the role of childhood adiposity in the associations of age at menarche with cardiometabolic health, with studies that have been able to do this suggesting that childhood BMI before puberty confounds any associations with adult BMI4, 14 and thus, potentially, with cardiometabolic risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another increasingly popular approach is Mendelian randomization, which addresses unmeasured and residual confounding by using genetic polymorphisms as instrumental variables for the exposure of interest, based on their random allocation at conception resulting in their independence of confounding factors 43. However, the potential to use Mendelian randomization to study age at menarche in relation to cardiometabolic health is hampered by the number of overlapping genes associated with both age at menarche and adiposity 20, 31. Longitudinal studies with measures of adiposity before and after puberty have the potential to contribute valuable insight into the role of childhood adiposity in the associations of age at menarche with cardiometabolic health, with studies that have been able to do this suggesting that childhood BMI before puberty confounds any associations with adult BMI4, 14 and thus, potentially, with cardiometabolic risk.…”
Section: Discussionmentioning
confidence: 99%
“…We did not have any direct measures of childhood socioeconomic position in GS:SFHS and thus had to rely on adult educational attainment as a proxy for childhood socioeconomic position. Under the assumption that there are genes that are common determinants of age at menarche and adverse cardiometabolic health, which is clearly the case for obesity‐related genes,20, 31 parental histories of CVD and diabetes mellitus were also conceptualized as confounders. We then explored further adjustment for adult lifestyle characteristics, including pack‐years of smoking, units of alcohol consumed during the past week, and number of hours of moderate or vigorous physical activity during the past week (model 3).…”
Section: Methodsmentioning
confidence: 99%
“…The E allele promoting earlier maturation is most abundant in males (EE most frequent, EL moderate, LL most rare), whereas in females the L allele promoting delayed maturation seems to be selected for (EE most rare, EL moderate, LL most frequent) (Barson et al., 2015). Interestingly, vgll3 is also associated with the onset of puberty and adiposity in humans (Cousminer et al., 2013), suggesting that this gene might be functionally highly conserved across vertebrates. Because late‐maturing fish with larger body mass (higher sea age) exhibit higher reproductive success and females mature later than males on average (Fleming & Einum, 2010), sea age is a trait of great interest to understand sexual conflict, that is, sex‐differential selection on a trait with a common genetic basis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, genome-wide association studies have identified genetic variants that are associated with obesity and greater BMI in adulthood. Since BMI changes in childhood can result from changes in both height and weight, examining the effect of the genetic variants on growth trajectories in childhood can provide improved understanding of the potential mechanisms through which the genes are acting (Paternoster et al 2011;Warrington et al 2013;Cousminer et al 2013). Risk scores of obesity-related genetic variants have been shown to be associated with changes in height, weight and BMI across infancy and childhood, with the magnitude of associations changing across the life course Elks et al 2010Elks et al , 2012Hardy et al 2010).…”
Section: Aetiological Insight From Studying Childhood Adiposity Trajementioning
confidence: 99%